Psychosocial Experiences of Women with Infertility and their Coping Strategies in Zamfara State, Nigeria. - Lawali, Y. (University of Ghana, 2015)
Globally, children are believed to have strong value especially among African societies. Therefore, the inability to bear children is a stressful situation that affects women socially, and psychologically, and puts them in a serious life crisis. Women with infertility have different experiences which vary from one country to the other including Nigeria, and that determine their psychosocial health. However, little is known about women`s experiences of infertility in Zamfara state. This calls for a major concern in exploring psychosocial experiences of women with infertility in Zamfara. The aim of this study was to explore the psychosocial experiences of women with infertility in Zamfara, Nigeria. Basic interpretive design of a qualitative approach was used to obtain information relevant to the research questions. Twelve (12) women who fulfilled the inclusion criteria were selected using a purposive sampling technique. Semi structured interview guide was administered to the women who fulfilled the inclusion criteria after filling out the consent form. The responses were elicited and analyzed using content analysis. The findings of this research revealed that, psychologically, majority of the women had experienced anxiety, stress and depression as a result of their inability to get pregnant. Socially, the women suffered social isolation, social stigma, social pressure and marital problems. The psychological experiences were linked to social experiences and were mostly from mother in-laws and husbands` relatives. Major coping strategies adopted by the women were spiritual, social support, informal child adoption and diversional coping strategies. The women in Zamfara sought help for their infertility from both traditional medicine and medical treatment. However, they frequently withdrew from treatment or changed the health facility due to perceived less benefit. Therefore, infertility needs to be seen as a public health problem rather than just a disease. The findings of this study have implications for nursing practice and nursing research.
Thesis (MPhil) -University of Ghana, 2016